Color Stability and Micro-Hardness of Bulk-Fill Composite Materials after Exposure to Common Beverages - Bahbishi, Nora (Materials (Basel), 2020)
Objectives: To assess the color stability and surface microhardness of Bulk-Fill composite materials available in the Saudi Arabia market. Methods: Five composite materials (Filtek Z350, Filtek Bulk-Fill, Tetric N-Ceram Bulk-Fill, Sonic Fill 2, and SDR) were investigated. Samples (n = 20; 10 mm in diameter and 2 mm in thickness) were fabricated using a stainless-steel mold and were immersed in tea, coffee, berry juice, and distilled water (control). Baseline (T(0)) shades of specimens were recorded using a spectrophotometer and after 10 (T(1)), 30 (T(2)), 60 (T(3)), and 90 days (T(4)) of immersion. Measurements were obtained against a black background and CIE L*a*b* data was used to calculate ΔE for each group. Vickers microhardness values were obtained at T(0) and T(4). Data was analyzed using mixed model repeated measure ANOVA at 0.05 significance level. Results: Time, material, and solution effects have statistically significant effect on ΔE. Tea was the most staining solution. Z350 was associated with the highest ΔE values while SDR showed the lowest values. No other materials showed significant difference between each other. Solutions were statistically different from each other. All materials were different from each other regarding microhardness. Conclusion: Bulk-Fill materials showed more color stability but lower microhardness values compared to universal resin control.